PERANCANGAN TEKNOLOGI REAKTOR PIROLISIS PENGUBAH SAMPAH PLASTIK MENJADI BAHAN BAKAR CAIR DALAM RANGKA MENGURANGI LIMBAH SAMPAH PERKOTAAN - Dori Yuvenda; Husnil Khatimah; Purwantono Purwantono; Durain Parmanoan (Universitas Muhammadiyah Ponorogo, 2026)
The problem of waste in urban areas has become a serious problem today, especially plastic waste that can damage the environment such as damaging terrestrial and marine ecosystems because plastic waste is difficult to decompose and takes a long time to decompose completely. Padang Panjang City is one of the densely populated cities that has the potential to produce large amounts of plastic waste. Through community service activities, the Padang State University service team provides a solution by presenting a tool for processing plastic waste into useful items, namely converting waste into liquid fuel. The UNP service team collaborates with KSM TPS 3R BUKISU Padang Panjang city as a service partner by presenting an innovative pyrolysis reactor tool for converting plastic waste into liquid fuel. The activity starts from a field survey related to problems with partners, designing waste conversion tools, manufacturing tools, handing over tools to partners, demonstrations and socialization of tools, testing tool performance, and monitoring and mentoring on tools that have been handed over to partners. The results of the community service activities have succeeded in creating a pyrolysis reactor unit that converts plastic waste into liquid fuel. Then, the performance of the pyrolysis reactor was tested. Where it can operate well, which is indicated by the liquid fuel produced after a 3-hour test. The resulting fuel has a calorific value close to gasoline, namely 7,965 kcal/kg and a fuel density of 735.9 kg/cm3.